Serological Survey of Hantavirus in Inhabitants from Tropical and Subtropical Areas of Brazil - Felipe Alves Morais; Alexandre Pereira; Aparecida Santo Pietro Pereira; Marcos Lazaro Moreli; Luís Marcelo Aranha Camargo; Marcello Schiavo Nardi; Cristina Farah Tófoli; Jansen Araujo; Lilia Mara Dutra; Tatiana Lopes Ometto; Renata Hurtado; Fábio Carmona de Jesus Maués; et al. (Advances in Virology)
Brazil has reported more than 1,600 cases of hantavirus cardiopulmonary syndrome (HPS) since 1993, with a 39% rate of reported fatalities. Using a recombinant nucleocapsid protein of Araraquara virus, we performed ELISA to detect IgG antibodies against hantavirus in human sera. The aim of this study was to analyze hantavirus antibody levels in inhabitants from a tropical area (Amazon region) in Rondônia state and a subtropical (Atlantic Rain Forest) region in São Paulo state, Brazil. A total of 1,310 serum samples were obtained between 2003 and 2008 and tested by IgG-ELISA, and 82 samples (6.2%), of which 62 were from the tropical area (5.8%) and 20 from the subtropical area (8.3%), tested positive. Higher levels of hantavirus antibody were observed in inhabitants of the populous subtropical areas compared with those from the tropical areas in Brazil.